1974
DOI: 10.1073/pnas.71.1.80
|View full text |Cite
|
Sign up to set email alerts
|

ACTH Antagonists

Abstract: Structural modifications within the active site of the ACTH molecule have produced analogs that inhibit the hormone sensitive adenylate cyclase system of bovine adrenal cortical plasma membranes. It is demonstrated that the tryptophan residue of the ACTH molecule is essential for stimulation of the enzyme. Substitution of tryptophan by phenylalanine or by NG-methyltryptophan as in [Gln5, provides ACTH analogs that exhibit high affinity for the ACTH receptor(s) but fail to activate the adenylate cyclase syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…When the sensitivity to hormonal stimulation of cyclic AMP production in intact adrenal cells (Mackie et al, 1972;Seelig & Sayers, 1973;Peytremann et al, 1973;Finn et al, 1976) is compared with that of the adenylate cyclase activity in membrane preparations from adrenal glands of the same species (Hoffmann et al, 1974;Londos & Rodbell, 1975;Dazord et al, 1975;Glossmann & Gips, 1975), the former system is commonly more sensitive. However, we have consistently found a KO.5 value in the range 0.3-1.0nM for all batches of bovine adrenal membranes.…”
Section: Adenylate Cyclasementioning
confidence: 99%
“…When the sensitivity to hormonal stimulation of cyclic AMP production in intact adrenal cells (Mackie et al, 1972;Seelig & Sayers, 1973;Peytremann et al, 1973;Finn et al, 1976) is compared with that of the adenylate cyclase activity in membrane preparations from adrenal glands of the same species (Hoffmann et al, 1974;Londos & Rodbell, 1975;Dazord et al, 1975;Glossmann & Gips, 1975), the former system is commonly more sensitive. However, we have consistently found a KO.5 value in the range 0.3-1.0nM for all batches of bovine adrenal membranes.…”
Section: Adenylate Cyclasementioning
confidence: 99%
“…It is worth noting here that HoFFMAN et al (184) recently found that a phenylalanine analog of ACTH was devoid of enzymatic activity, but exhibited affinity for the ACTH receptor. For these reasons, Cov et al (90) suggested that the essential feature oftryptophan in maintaining hormonal action was due to its electron-donating properties.…”
Section: 3luteinizing Hormone-releasing Hormonementioning
confidence: 96%
“…Shorter peptides ACTH 1-24 and ACTH 1-23 were shown to have agonist properties similar to that of the full length ACTH, whereas a 13-residue peptide ACTH 11-24 was shown to have antagonist properties (Table 2) [29]. It was also shown that a peptide with an N-methyltryptophan instead of Trp at the 9 position in ACTH 1-24 had antagonist activity [30]. In a recent study by Kovalitskaya et al , it was shown that the cationic C-terminal sequence -Lys-Lys-Arg-Arg- (ACTH 15-18 ) had antagonist activity [31].…”
Section: Human Mc2r Antagonistsmentioning
confidence: 99%